2018
DOI: 10.3389/fnhum.2018.00202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcutaneous Vagus Nerve Stimulation (tVNS) on the P300 and Alpha-Amylase Level: A Pilot Study

Abstract: Recent research suggests that the P3b may be closely related to the activation of the locus coeruleus-norepinephrine (LC-NE) system. To further study the potential association, we applied a novel technique, the non-invasive transcutaneous vagus nerve stimulation (tVNS), which is speculated to increase noradrenaline levels. Using a within-subject cross-over design, 20 healthy participants received continuous tVNS and sham stimulation on two consecutive days (stimulation counterbalanced across participants) whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(173 citation statements)
references
References 122 publications
8
135
3
3
Order By: Relevance
“…Our results compliment work by Ventura-Bort and colleagues [17], who reported preliminary evidence that taVNS increases SAA. We demonstrate a more robust effect, using a larger sample size (25 vs. 18 participants), more post-stimulation saliva samples (2 vs. 1), and a superior method of saliva collection (whole saliva method vs. absorbent cotton sponges) [9,51].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results compliment work by Ventura-Bort and colleagues [17], who reported preliminary evidence that taVNS increases SAA. We demonstrate a more robust effect, using a larger sample size (25 vs. 18 participants), more post-stimulation saliva samples (2 vs. 1), and a superior method of saliva collection (whole saliva method vs. absorbent cotton sponges) [9,51].…”
Section: Discussionsupporting
confidence: 93%
“…The oddball P3 was larger in the taVNS condition (7.6 μV) than in the sham condition (6.5 μV). This difference was not significant, F (1,17)=2.32, p=.15 (Fig. 3).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the study of patient groups may give only partial insight into typical neuromodulatory mechanisms because key neural circuitry may already be compromised by disease or injury. Recently, Ventura-Bort and colleagues examined the impact of auricular transcutaneous VNS on P300b in neurotypical subjects, with data indicating that stimulation significantly increases P300b amplitude to easy targets (91). Importantly, this study also found VNS related increases in salivary alpha-amylase, an independent indirect marker of noradrenergic activity.…”
Section: Wwwneuromodulationjournalcommentioning
confidence: 81%
“…Participants were required to rate their subjective sensation of the stimulation intensity after each adjustment of 0.1 mA on a visual 11-point scale, ranging from nothing (0), light tingling (3), strong tingling (6) to painful (10). The tVNS workup lasted until the participants reported a "tingling" sensation of 8, after which they underwent a 30 s ON and 30 s OFF stimulation protocol to experience the stimulation as it would be during the extinction training 47 . If the participant still reported a sensation of 8 after the protocol, the adjusted intensity was used during extinction training.…”
Section: Extinction Training (Session 2)mentioning
confidence: 99%